Controllable synthesis of ZnO nanoflowers and their morphology-dependent photocatalytic activities - Wang, Y.; Li, Xin Yong; Wang, N.; Quan, X.; Chen, Y. (Pergamon Press, 2008)
ZnO nanoflowers were successfully synthesized by a simple low-temperature route in the absence of surfactants. Systematic experiments were carried out to investigate the factors that affect the morphology of the samples. It is demonstrated that ZnO with different morphology such as flowers and rods can be controllable obtained by simply varying the basicity in the solution. The as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and selected area electron diffraction (SAED). It has been found that the ZnO nanoflowers contain many radial nanorods with the diameter of 100 nm and the length of 1-1.5 µm and these ZnO single-crystalline nanorods with wurtzite structure grow along the [0 0 0 1] direction. The formation mechanism of ZnO nanoflowers and nanorods was initially interpreted in terms of the general theory of the crystal nucleation and crystal growth direction. ZnO with flower-like morphology exhibited improved ability on the photocatalytic degradation of 4-cholrophenol (4-CP) in aqueous solution under UV radiation compared with ZnO nanorods. The higher photocatalytic activity of the ZnO nanoflowers result from the larger content of oxygen vacancy on the surface of 1D nanomaterials as revealed by their Raman and Photoluminescence (PL) spectra features. It is thought that oxygen vacancy may act as the active centers of the catalyst, which could capture photo-induced electrons, whereas the recombination of photo-induced electrons and holes can be effectively inhibited. © 2008 Elsevier B.V. All rights reserved.